What aspects of intentional rounding work in hospital wards, for whom and in what circumstances? A realist evaluation protocol. Issue 1 (9th January 2017) - Harris, Ruth; Sims, Sarah; Levenson, Ros; Gourlay, Stephen; Ross CBE, Fiona; Davies, Nigel; Brearley, Sally; Favato, Giampiero; Grant, Robert
Abstract : Introduction: Intentional rounding (IR) is a structured process whereby nurses in hospitals carry out regular checks, usually hourly, with individual patients using a standardised protocol to address issues of positioning, pain, personal needs and placement of items. The widespread implementation of IR across the UK has been driven by the recommendations of the Francis Inquiry although empirical evidence of its effectiveness is poor. This paper presents a protocol of a multimethod study using a realist evaluation approach to investigate the impact and effectiveness of IR in hospital wards on the organisation, delivery and experience of care from the perspective of patients, their family members and staff. Methods and analysis: The study will be conducted in four phases. Phase 1: theory development using realist synthesis to generate hypotheses about what the mechanisms of IR may be, what particular groups may benefit most or least and what contextual factors might be important to its success or failure which will be tested in subsequent phases of the study. Phase 2: a national survey of all NHS acute trusts to explore how IR is implemented and supported across England. Phase 3: case studies to explore how IR is implemented 'on the ground', including individual interviews with patients, family members and staff, non-participant observation, retrieval of routinely collected patient outcomes and cost analysis. Phase 4: accumulative data analysis across the phases to scrutinise data for patterns of congruence and discordance and develop an overall evaluation of what aspects of IR work, for whom and in what circumstances. Ethics and dissemination: The study has been approved by NHS South East Coast—Surrey Research Ethics Committee. Findings will be published in a wide range of outputs targeted at key audiences, including patient and carer organisations, nursing staff and healthcare managers.